KAJIAN PENGGUNAAN NAUNGAN DAN MULSA TERHADAP IKLIM MIKRO PADA TANAMAN TOMAT (Lycopersicum esculentum Mill.) - Dita Rani Suryaningsih; Yosefina Mangera (Faculty of Agriculture, Musamus University, 2020)
ABSTRACT The purpose of this study is to determine the effect of shading and mulching on microclimates in tomato plants. This study used a Randomized Block Design (RBD) method with shade and mulch treatment consisting of 6 levels of treatment namely shade without mulch (NTM), plastic mulch shade (NMP), straw mulch shade (NMJ) and without shade without mulch (TNTM) , without plastic mulch shade (TNMP), without straw mulch shade (TNMJ). Each treatment was repeated three times so that there were 18 experimental units. The parameters observed in this study are plant parameters including plant height, number of branches, age of flowering, number of fruit plants and plant fruit weight. Microclimate observations include measurements of soil moisture, soil temperature, ambient temperature and humidity, wind speed and light absorption. Soil physical and chemical properties observed included soil texture, volume weight, specific gravity, soil pH, available K, porosity, organic matter, total N, field capacity and withering point. The results showed that the use of shade and mulch affected the soil moisture content. Shade can also reduce air temperature and can increase humidity. At the soil temperature the use of shade is very influential because it can reduce soil temperature, while the use of mulch also affects because it can reduce the radiation received and absorbed by the soil so that it can reduce soil temperature. Shade affects the speed of the wind and the absorption of light, where the speed of the wind and the absorption of light that is in the shade is lower than in the shade. Data on growth and production of tomato plants were analyzed using variance and tested further using a BNT advanced level of 5%. The use of shade and mulch has a very significant effect on the plant height observation variable at the age of 52 days after planting, but it does not have a significant effect on the observed variables of the number of branches, flowering age, number of fruits and fruit weight in tomato plants (Lycopersicum esculentum Mill). A good mulch for tomato plant growth is silver black plastic mulch, while a good mulch for tomato plant production is rice straw mulch.